Winged bean – a new soybean for the tropics? Genomic analysis for improving nutritional value and breeding efficiency in Psophocarpus tetragonolobus seeds - Tsoutsoura, Niki (2025)
Climate change, population growth, and lack of nutritional diversity in diets present significant challenges to food security and human health. The need for alternative protein sources is urgent, and the underutilised winged bean (Psophocarpus tetragonolobus (L.) DC.) grown in tropical regions emerges as a promising candidate due to its high nutritional profile. With high protein content ranging from 30-40% and oil content of 15-20%, winged bean could play a critical role in enhancing dietary diversity and addressing nutritional deficiencies. This thesis assessed the nutritional composition and in vitro digestibility of winged bean seeds; identified for the first time QTLs linked to nutritional traits such as protein and oil; and performed transcriptomic analysis on developing pods and seeds for the first time.